Three new species of tube-dwelling spider genus Ariadna Audouin, 1826 (Araneae: Segestriidae) from India - Siliwal, Manju; Yadav, Archana; Kumar, Dolly (Zootaxa, 2017)
The tube-dwelling spider family Segestriidae is represented in India by only two species, Ariadna nebulosa Simon, 1906 and Segestria inda Simon, 1906. Both species are known only from their type localities. For about 96 years, there has been no report of these spiders from the Indian subcontinent. Here, we describe three new species based on female specimens from India. Ariadna vansda sp. nov. from Gujarat; A. molur sp. nov., and A. chhotae sp. nov. from Karnataka.